Synthesis and evaluation of a series of resveratrol analogues as potent anti-cancer agents that target tubulin1. Issue 5 (13th May 2015) - Madadi, Nikhil R.; Zong, Hongliang; Ketkar, Amit; Zheng, Chen; Penthala, Narsimha R.; Janganati, Venumadhav; Bommagani, Shobanbabu; Eoff, Robert L.; Guzman, Monica L.; Crooks, Peter A.
<x xml:space="preserve">Abstract</x> Novel resveratrol analogues have been synthesized and evaluated for their anticancer activities against a panel of 60 human cancer cell lines.